Pengaruh Pendapatan Asli Daerah (PAD) dan Alokasi Dana dari Pusat terhadap Tingkat Kemiskinan di Provinsi di Yogyakarta Tahun 2015-2020 - Nur Fita Lindrianti (Universitas Diponegoro, 2022)
DI Yogyakarta Province is a province with the highest percentage of poverty in Java. This study aims to analyze the effect of Regional Original Income and Fund Allocation from the Center which consists of General Allocation Funds, Special Allocation Funds, and Revenue Sharing Funds on the poverty level in the Province of DI Yogyakarta in 2015-2020. Based on the data, This research is using panel of data after testing on Eviews 12.0, The most precise analysis is using panel data regression method. This research is using secondary data which consist of The real income profit, general fund, allocation fund, and sharing profit of 5 districts / city in Yogyakarta province 2015 - 2020. The result of this research is the allocation fund has positive effect on the poverty level, while the Regional Original Revenue, General Allocation Fund and Revenue Sharing Fund had no significant effect on the poverty level.